2020
DOI: 10.1002/lary.28524
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Cleft Width and Volume: Possible Risk Factors for Postinfectious Olfactory Dysfunction

Abstract: Objectives/Hypothesis Upper respiratory tract infections are a common cause of temporary and permanent olfactory dysfunction in the general population. Postviral or postinfectious olfactory loss (PIOL) develops only in rare cases. The aim of this study was to investigate the anatomical features of olfactory cleft (OC) in patients with PIOL to shed light on possible predisposing factors for PIOL. Study Design Retrospective study. Methods We retrospectively evaluated paranasal sinus computed tomography (CT) scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 20 publications
(49 reference statements)
2
27
0
Order By: Relevance
“…Among the countless existing theories, the most notable ones include olfactory cleft syndrome and postviral anosmia syndrome. 111 The former theory advocates on mucosal obstruction at the olfactory cleft results in conduction impairment of smell, 112 while the latter proposes on a neural loss mechanism whereby direct injury to the olfactory sensory neurons preceding viral infection. 113 It is noteworthy that postviral olfactory loss (PVOL) is not a novel phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Among the countless existing theories, the most notable ones include olfactory cleft syndrome and postviral anosmia syndrome. 111 The former theory advocates on mucosal obstruction at the olfactory cleft results in conduction impairment of smell, 112 while the latter proposes on a neural loss mechanism whereby direct injury to the olfactory sensory neurons preceding viral infection. 113 It is noteworthy that postviral olfactory loss (PVOL) is not a novel phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy provides valuable visualization of the nasal passageway that might reveal the presence of an obstruction, mucosal inflammation, polyps, or even malignancies that may obstruct the olfactory cleft. 10,22 These practice changes place the otolaryngologist and the patient in unique predicament.…”
Section: Discussionmentioning
confidence: 99%
“…52 Increase in olfactory cleft (OC) width and volume was noted to be a potential risk factor for PVOD. 46 Three studies demonstrated significant reduction in OB volume in patients with PVOD, 48,50,51 and that greater duration of PVOD led to greater reduction in OB volume. 48,51 Finally, one study showed that metabolic activities of higher olfactory centers were reduced following PVOD.…”
Section: Human Studiesmentioning
confidence: 99%